2014
DOI: 10.1097/nmd.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Self-assessment of Affective State in Different Phases of Bipolar Disorder

Abstract: Some studies have indicated that the capacity of self-assessment of affective state is more compromised during mania than during depression. In the present study, we investigated whether the reliability of self-assessment in bipolar disorder varies as a function of actual affective state (i.e., euthymia, mania, or depression). Sixty-five patients with a diagnosis of type I and type II bipolar disorder were evaluated with regard to the occurrence of an affective syndrome using the Clinical Global Impressions Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…In past studies, the preservation of insight in the depressive phase of BD has also been observed. 7,16,17 The development of the ISAD was based on the SUMD. 1 The SUMD, in turn, was developed to be applied in studies involving patients with schizophrenia and were significantly associated with high levels of insight impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past studies, the preservation of insight in the depressive phase of BD has also been observed. 7,16,17 The development of the ISAD was based on the SUMD. 1 The SUMD, in turn, was developed to be applied in studies involving patients with schizophrenia and were significantly associated with high levels of insight impairment.…”
Section: Discussionmentioning
confidence: 99%
“…However, evaluation of insight through the use of self-evaluation instruments may result in discrepancies when compared with objective evaluations. 16,17 In light of these different measurement tools, Olaya et al 18 developed the Insight Scale for Affective Disorders (ISAD), which relies on hetero-application for patients with mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Another study which was done to evaluate insight in mania, depression and euthymia in 95 bipolar affective disorder patients showed poor insight among mania patients when compared with depressive patients. [ 19 ] The P value was significant 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…The median prevalence of nonadherence is 44.7% in patients with bipolar affective disorder. [ 19 ] In one study that was done to assess the predictors of nonadherence in bipolar affective disorder patients showed treatment nonadherent individuals had more negative attitudes toward medications and reduced insight into illness when compared with treatment adherent individuals. [ 20 ] We also compared the MDIS scores between good compliance and poor compliance group.…”
Section: Discussionmentioning
confidence: 99%
“…Brown, et al 39 Somewhat related to the question with regards to sensitivity to minor changes is the observation made by de Assis da Silva et al 66 who found that patients in a manic and euthymic state responded very similar on visual analog scales of mood. This raises the issue of which individual questions and items help differentiate between mood states or between normal and clinically relevant elated states, especially in outpatient samples.…”
Section: Limitationsmentioning
confidence: 99%